Strategi Pengelolaan Stres Perawat selama masa Pandemi COVID-19 : Studi Febomenologi: Strategi Pengelolaan Stres Perawat selama masa Pandemi COVID-19 : Studi Febomenologi - Sekani Niriyah; Hema Malini; Feri Fernandes; Heppi Sasmita (LPPM Hang Tuah Pekanbaru, 2022)
The COVID-19 pandemic is spreading rapidly almost all over the world and has an effect on all aspects, especially in health services. Nursing is the profession with the highest interaction time with COVID-19 patients and is the profession that reports the most psychological impacts due to the pandemic. Changes in treatment procedures, working in areas of risk of infection and the unpredictability of this pandemic have become a source of stress for nurses. Nurses are required to be able to manage the stress they feel in maintaining mental health and optimizing services. This study is part of a qualitative method that explores experiences related to nurses' stress management strategies during the COVID-19 pandemic. The research participants were 9 people, namely nurses who worked in the COVID-19 treatment room and were selected based on the purposive sampling technique. The study was conducted at 3 hospitals in Pekanbaru and started at the end of June 2021 until early August 2021. Data collection was carried out by interviewing techniques and data analysis techniques using Collaizy analysis. The results of this study indicate that doing activities that you like, telling stories with others, taking vitamins, and taking time to rest are strategies that are used to manage perceived stress. Nurses are able to perform good stress management in an effort to maintain mental health during the pandemic. Cooperation from various parties is needed to achieve success in dealing with the pandemic.